An Analysis of Using Movies to Enhance Students’ Public Speaking Skills in Online Class - Putri Rindu Kinasih; Olivia Olivia (Journal of Languages and Language Teaching, 2022)
Despite the importance of public speaking skills, unfortunately, research about public speaking classes mainly focuses on the attempt to minimize the students’ anxiety and discomposure. Whereas other crucial issues need to be investigated such as the quality of learning materials in public speaking classes having poor quality and students’ difficulty in speaking naturally. This research aimed to investigate the usage of movies in enhancing students’ ability to deliver speeches. The participants of this study are 67 students majoring in English Language and Literature consisting of 46 females and 21 males. All participants were taking the listening-speaking class and public speaking class. This study adopts the mixed-method approach. Firstly, to see the progress of students’ public speaking skills, we conducted a pre-test and post-test which were analyzed based on a scoring rubric proposed by Joe et al. In addition, questionnaires were distributed to understand participants’ perceptions after learning about public speaking through movies. Lastly, a semi-structured interview was done to enrich the discussion. The results showed that movie clips are effective in increasing students’ interest in following an online class because the lesson felt contextual. The participants’ public speaking skills also improved as students can apply the strategies to attract audiences.